Minas na Semi: (re) significações das narrativas das adolescentes em cumprimento da medida socioeducativa semiliberdade - Rebeca Cristina Nunes Lloyd Gonçalves (2019)
In Brazil, cautious adolescents are institutionally among the most vulnerable segments. This research was carried out in a House of Semiliberdade of the city of Belo Horizonte - Minas Gerais, taking as object of study the narratives of the adolescents in fulfillment of socioeducative measure, in closed environment. Since the masculine and the feminine constitute fields structured in the relations of power, gender relations are one of the most important and permanent asymmetries of modern society, being one of the structuring elements of social institutions (SCOTT, 1994). The research sought to detect the peculiarities of the measure of semi - freedom in the processes experienced by adolescents in situations of vulnerability and conflict with the law, analyzing, through their narratives, their perceptions and trying to understand how they construct (re) significations about themselves, educational processes and the world. It was characterized by a qualitative approach (MINAYO, 1994), using direct observation (LAKATOS, 2003), documentary research (GIL, 1999), narrative interviews (MINAYO, 2012), intervention research (AGUIAR, 2007) and the circular processes (PRANIS, 2010). The reports pointed out clues about the way in which adolescents institute their experiences in the house, from syntheses of social issues lived in the singularity of the youthful experiences. We noticed that the narratives directed our look at some aspects that mark and influence the life of the "Minas na Semi". Fulfilling the socio-educational measure is a situation and not a condition in which they are immersed. In this sense, the semi-liberty house appears as a territory in which they construct forms of belonging. Strategies of re (meaning) and resilience are daily experienced and generalized, because they are young adolescents, girls and poor in compliance with socio-educational measure. The intervention process allowed the construction of two products, which are the record of the methodology developed in the interventions of the participatory research, with the purpose of divulging in the semiliberty houses and door pillows constructed by the adolescents in the circular processes through the artistic experiences and wheels of conversation.